The Canada-Guyana medical education partnership: using videoconferencing to supplement post-graduate medical education among internal medicine trainees - Stokes, William; Ruzycki, Shannon; Jainarine, Ramdeo; Isaac, Debra; Cole, Joanna (Canadian Medical Education Journal, 2017)
Background: A Guyana-based, internal medicine (IM) post-graduate medical education program was established in 2013. However, lack of formal teaching sessions are barriers to the program’s success. Objective: To describe the partnership between the University of Calgary and the University of Guyana’s internal medicine residency programs (IMRP). This partnership was created to support the Guyana’s IM academic half-day and is characterized by mutually beneficial, resident-led videoconference teaching sessions. Methods: Calgary medical residents volunteered to create and present weekly teaching presentations to Guyanese residents via videoconference. Questionnaires were completed by Guyanese residents and provided to Calgary residents as feedback on their teaching and presentation skills. A similar survey was completed by Calgary residents. Lessons learned: Twenty-four videoconference teaching sessions were conducted over eight months with a total of 191 and 16 surveys completed by Guyana and Calgary residents, respectively. Over 92% of both Guyana and Calgary residents agreed that the sessions enhanced their learning and over 93% reported increased interest in becoming more involved in international collaborations. 88% of Calgary residents felt the sessions improved their teaching skills. Conclusion: The formation of a resident-led, videoconference teaching series is a mutually beneficial partnership for Canadian and Guyanese medical residents and fosters international collaboration in medical education.